2014
DOI: 10.1007/s10551-014-2177-9
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Framework to Understand How CSR Affects Customer Loyalty through Identification, Emotions and Satisfaction

Abstract: Because previous scholars have offered few comprehensive models to understand the benefits of corporate social responsibility image in terms of customer behaviour, the authors of this paper propose a hierarchy of effects model to study how customer perceptions of the social responsibility of companies influence customer affective and conative responses in a service context. The authors test a structural equation model using information collected directly from 1,124 customers of banking services in Spain.The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
183
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 58 publications
18
183
1
2
Order By: Relevance
“…The number of relevant studies on the relationship in the retail banking industry is significantly larger than in the mobile telecommunications sector, the research focus being on developed countries such as Spain (Matute-Vallejo, Bravo, & Pina, 2011;Pérez, de los Salmones, & del Bosque, 2013;Pérez & del Bosque, 2015), Austria (Öberseder, Schlegelmilch, Murphy, & Gruber, 2014), the U.S.A. (Choi & La, 2013;Walsh & Beatty, 2007), Australia (Chomvilailuk & Butcher, 2014) and the U.K. (Ruiz et al, 2016). Thus, Matute-Vallejo et al (2011), as well as and Pérez and del Bosque (2015), concluded that the social and environmental facets of perceptual corporate sustainability positively impact customer loyalty, the relationship being mediated by consumer-company identification and customer satisfaction.…”
Section: The Relationship Between Perceptual Corporate Sustainabilitymentioning
confidence: 99%
“…The number of relevant studies on the relationship in the retail banking industry is significantly larger than in the mobile telecommunications sector, the research focus being on developed countries such as Spain (Matute-Vallejo, Bravo, & Pina, 2011;Pérez, de los Salmones, & del Bosque, 2013;Pérez & del Bosque, 2015), Austria (Öberseder, Schlegelmilch, Murphy, & Gruber, 2014), the U.S.A. (Choi & La, 2013;Walsh & Beatty, 2007), Australia (Chomvilailuk & Butcher, 2014) and the U.K. (Ruiz et al, 2016). Thus, Matute-Vallejo et al (2011), as well as and Pérez and del Bosque (2015), concluded that the social and environmental facets of perceptual corporate sustainability positively impact customer loyalty, the relationship being mediated by consumer-company identification and customer satisfaction.…”
Section: The Relationship Between Perceptual Corporate Sustainabilitymentioning
confidence: 99%
“…These two features are outlined in the European Commission's (2002) definition of CSR as the voluntary integration by organizations of social and environmental concerns in their business processes and their relationships with their stakeholders (25) . This concept of CSR stresses that organizations should pay special attention to economic, social, and environmental aspects in their strategic planning (26)(27)(28).…”
Section: Conceptual Bases: the Definition Of Csr And The Role Of Contextmentioning
confidence: 99%
“…Highlighted aspects include the country-level institutional factors [92], the role that governments can play [93], institutional pressure [10,94] and developing an institutional framework [8]. (3) Reputation management: CSR has a positive effect on corporate reputation [36], and lowering the cost of capital [95], on loyalty [29] with the integration of the organization into its host community [27] on improving firms' reputations in relation to their stakeholders [96,97] and their performance in the eyes of governments [98]. This is also one of the most commonly mentioned aspects as a CSR driver, cited in 13.6% of the papers.…”
Section: Drivers Of and Barriers To Csr Strategies: Content Analysismentioning
confidence: 99%
“…This study aims to fill some of these gaps by developing a tool that enables us to explain the socially responsible behavior of companies, considering CSR in relation to its drivers/barriers. This is achieved by analyzing solidarity [27], preventing incident-induced reputation risks [28], promoting customer loyalty [29], etc. On the other hand, based on instrumental stakeholder theory, most of the barriers that hinder the development of CSR in firms are related to property rights and the maximization of shareholder value [14,21].…”
Section: Introductionmentioning
confidence: 99%